COFFEE FARMING EFFICIENCY USING A COBB–DOUGLAS MODEL RECOMMENDATION SYSTEM - Oktanita Jaya Anggraeni; Dewi Kurniawati; Wenny Dhamayanthi; Rizal Perlambang CNAWP (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
Smallholder coffee farming has a significant contribution to the rural economy, but the efficiency of input use is still a major challenge. This study aims to analyze the influence of production factors on the results of smallholder coffee farming in Suci Village, Panti District, Jember Regency, and to design and implement an input optimization model based on the Cobb-Douglas production function in the form of a simple and practical recommendation system. The novelty of this study lies in the application of economic production functions into a recommendation system that is easy for farmers to operate. The research method used is a quantitative approach, with regression analysis of the Cobb-Douglas model and a spreadsheet-based system implementation test on ten coffee farmers. The results showed that labor, fertilizer, capital, and land had a significant influence on crop yields, with labor as the most dominant factor. However, only labor was used excessively, while other inputs were still underutilized. The implementation of the system resulted in an increase in productivity of 28.5% and economic efficiency of 35.5%, while helping farmers understand the difference between actual and optimal inputs. This study shows that the integration of production functions and practical recommendation systems can be an efficient and applicable solution for decision making in community coffee farming.